Underactuated Mechanical Systems -- A Review of Control Design - Zhang, Zilong; Suh, C. Steve (Journal of Vibration Testing and System Dynamics, 2026)
An active research subject in robotics and aeronautics, underactuated mechanical systems (UMS) have been extensively explored for applications where maintaining stability and safety is of paramount importance. All contemporary control methodologies of recent have been applied to controlling various UMS designs. A great amount of effort is documented on a yearly basis by journals and conference proceedings claiming to offer effectively better solutions to improved UMS control. However, control design for UMS is still considered an open problem due to issues including parametric uncertainty, coupled nonlinear dynamics, and need for fewer control actuators. This presentation presents a comprehensive survey on the present state-of-affairs pertaining to the control of UMS of different configurations. Relevant references in the open literature dating as far back as 1990 are reviewed and meticulously categorized. Popular underactuated control techniques are reviewed, and their primary features re-examined, for their strengths and where they fall short in addressing properties of underactuation including coupled dynamics, nonlinearity and non-stationarity. No prior review articles have provided similarly critical while also in-depth review of published works on UMS control. This survey serves as an expanded reference for researchers and practitioners who seek to control UMS with efficacy.